Evaluasi Sepuluh Tahun Reformasi Polri - Siregar, Sarah Nuraini (Jurnal Penelitian Politik, 2008)
The reform of the Indonesian Police Institution (Polri) was one of the Indonesian 'reformasi' deniand that began in 1998. This aspect was the reason behind the emergence of nnanv policies related with efforts to reform Polri in structural, instrumental and cultural aspects. These efforts were part of internal refornn of Polri and admittedly, it showed that there has been significant changes in Polri in terms ofits organisation system. However, these efforts have not been able to create maximum results due to some constraints, not only from internal Polri, but also from government regulation assumed to be normative. As a consequence, there were still barriers for Polri to fulfill the 'reformasi' demand and to act in proportional and professional way.